2018
DOI: 10.1021/acs.energyfuels.7b04076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Influence of the Ethanol Concentration on the Flame Structure and Soot Precursor Formation of the n-Heptane/Ethanol Premixed Laminar Flame

Abstract: The purpose of this work is to investigate the effect of the ethanol blending ratio on the flame structure (species concentrations, heat release rate, and flame temperature profile) and soot precursor (CH 3 , C 2 H 2 , aC 3 H 5 , and C 3 H 3 ) formation of the n-heptane/ethanol premixed laminar flame at the equivalence ratio of 2 and pressure of 3.861 MPa. The results indicate the following: First, n-heptane consumes more rapidly than ethanol for its high dehydrogenation reaction rate under the research temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…They also investigated the effect of fuel type and blending ratio on combustion characteristics and soot precursor formation on a CVV. 32,33 Lee et al 34−36 studied the flame development, combustion, and gas phase emission characteristics of hydrogen compressed natural gas. Furthermore, the CVV can be used to study the laminar burning velocities of gas phase fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also investigated the effect of fuel type and blending ratio on combustion characteristics and soot precursor formation on a CVV. 32,33 Lee et al 34−36 studied the flame development, combustion, and gas phase emission characteristics of hydrogen compressed natural gas. Furthermore, the CVV can be used to study the laminar burning velocities of gas phase fuels.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a CVV can satisfy the systematic research on fuel combustion characteristics and emission characteristics. They also investigated the effect of fuel type and blending ratio on combustion characteristics and soot precursor formation on a CVV. , Lee et al studied the flame development, combustion, and gas phase emission characteristics of hydrogen compressed natural gas. Furthermore, the CVV can be used to study the laminar burning velocities of gas phase fuels. The studies above show that the CVV can meet the requirements of measuring the gas phase emissions and particulate matter from fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…us, some oxygen-containing intermediate radicals may be evolved in the combustion, which further promoted the oxidation of basic carbon particles. In addition, particle size is also affected by fuel and the flow rate of oxidizer, since the change in their initial velocity will affect the combustion reaction and the time of the soot particles staying in the flame [16]. Increasing the velocity of the oxidizer can suppress the energy transfer from the annular region producing soot to the flame axis.…”
Section: Analysis Of the Distribution Of Soot Sizesmentioning
confidence: 99%
“…Ergut et al [15] investigated the generation of polycyclic aromatic hydrocarbons (PAHs) in ethylbenzene and ethanol flame at atmosphere pressure and pointed out that the generation rate of PAHs of ethanol was low even under lean oxygen combustion. Previous studies investigated the influence of ethanol doping ratio on the flame structure of n-heptane/ethanol and the formation rate of soot precursor [16]. It was found that the dehydrogenation rate of n-heptane was faster than that of ethanol, while ethanol promotes the reaction by providing active free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [12] studied the impact of ethanol vapor additions into the laminar diffusion flame of n-heptane on the mass yield of soot particles, as well as on their structure and morphology. Research results have shown that the addition of ethanol has a direct effect on the flame height and the size of the resulting soot particles.…”
Section: Introductionmentioning
confidence: 99%